Entrepreneurial attitude and success in the Colombian auto parts sector (Dimensión Empresarial, 2020)
The growth, transformation and development of new economic sectors of a country can be determined from the entrepreneurship. This entrepreneurial attitude manifests itself from different approaches, not only by the emergence of new companies, but also by decision-making and entrepreneurial activity, in certain situations. Business success can be attributed to the different influences, changes and pressures caused by the environment, or to special characteristics of entrepreneurs, personal aspects and environment. This article aims to analyze intra-entrepreneurship as a business renewal strategy, exploring the auto parts sector, through a qualitative study in a sample of companies in the auto parts sector in Colombia. The results conclude that despite the fact that intra-entrepreneurship is considered a strategic scenario for business renewal, Colombian auto parts companies do not promote their strategic development.